1996
DOI: 10.3758/bf03206821
|View full text |Cite
|
Sign up to set email alerts
|

Intentional versus unintentional use of contingencies between perceptual events

Abstract: In three experiments we studied human ability to use statistical contingencies between visual stimuli (flankers and targets) to improve performance in a letter-digit classification task. We compared the performance of explicitly informed subjects with that of subjects who were told nothing of the contingencies. Simultaneous presentation offlankers and targets (Experiment 1) produced evidence of unintentional contingency use by both informed and uninformed subjects. When stimuli on trial n predicted target stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 6 publications
(10 reference statements)
0
37
3
Order By: Relevance
“…Thus, the better performance on high relative to low contingency trials seems to be a case of implicit learning. Similar reports of learning without awareness have been found in a wide array of performance (i.e., response time) paradigms, such as the Eriksen flanker task (Carlson & Flowers, 1996;Miller, 1987), serial response time task (Destrebecqz & Cleeremans, 2001;Jiménez & Méndez, 1999;Mayr, 1996;Nissen & Bullemer, 1987;Song, Howard, & Howard, 2007; Willingham, Nissen, & Bullemer, 1989), and hidden covariation detection tasks (Lewicki, 1985(Lewicki, , 1986Lewicki, Hill, & Czyzewska, 1992), along with other paradigms such as the Hebb digits task (McKelvie, 1987).…”
Section: Does Matter In the Colour-word Contingency Learning Paradigmmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, the better performance on high relative to low contingency trials seems to be a case of implicit learning. Similar reports of learning without awareness have been found in a wide array of performance (i.e., response time) paradigms, such as the Eriksen flanker task (Carlson & Flowers, 1996;Miller, 1987), serial response time task (Destrebecqz & Cleeremans, 2001;Jiménez & Méndez, 1999;Mayr, 1996;Nissen & Bullemer, 1987;Song, Howard, & Howard, 2007; Willingham, Nissen, & Bullemer, 1989), and hidden covariation detection tasks (Lewicki, 1985(Lewicki, , 1986Lewicki, Hill, & Czyzewska, 1992), along with other paradigms such as the Hebb digits task (McKelvie, 1987).…”
Section: Does Matter In the Colour-word Contingency Learning Paradigmmentioning
confidence: 78%
“…If true, this would mean that the colour-word contingency learning paradigm is exactly the type of paradigm mostly likely to be immune to conscious contingency knowledge. In line with this idea, paradigms in which the distracter is presented in advance of the target do often show a positive effect of contingency knowledge, for instance, in a flanker task where flankers were presented in advance of the target (Carlson & Flowers, 1996, Experiment 3) and in sequence learning (e.g., Mayr, 1996).…”
Section: Learning Awareness and Instruction: Subjective Contingencymentioning
confidence: 86%
See 1 more Smart Citation
“…This suggests that, independent of the participant's awareness of the task manipulation, the processes involved in learning are implicit. A similar argument has been made from results of a flanker task in which flanking cues were predictive of the response (Carlson & Flowers, 1996), sequence learning (Song, Howard Jr., & Howard, 2007), and other paradigms (e.g., Lewicki, Hill, & Czyzewska, 1992). However, the role of awareness in contingency learning is a highly controversial issue.…”
Section: Introductionmentioning
confidence: 85%
“…Of interest in the correlated flanker task are responses to two types of trials: valid trials, in which the flankers are highly correlated with the same response as that required by the target (and, therefore, validly cue the target response), and invalid trials, in which the flankers are highly correlated with the other response (and, therefore, invalidly cue the target response). Research with the correlated flanker task has shown that response times are slowed to targets on invalid trials, relative to valid trials (e.g., Carlson & Flowers, 1996;Miller, 1987Miller, , 1991Paquet & Lortie, 1990;Schmidt & Dark, 1998;Stadler & Proctor, 1993). That is, response times showed that participants are influenced by the flanker-response correlations.…”
Section: Flanker Recall and The Flanker Validity Effect May Reflect Dmentioning
confidence: 99%